2012
DOI: 10.1108/17542411211199264
|View full text |Cite
|
Sign up to set email alerts
|

Sex role stereotypes: does business education make a difference?

Abstract: Purpose -Studies indicate that a managerial pro-male bias still exists. While managers and females have begun to view women as possessing managerial attributes, male students, on average, still tend to stereotype the managerial role using a pro-male bias. Based on research by Heilman and by Lord and Maher, the purpose of this paper is to propose that business students, who are exposed to a curriculum that emphasizes the importance of diversity, as recommended by AACSB, will exhibit fewer gender stereotypes. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…These cases simultaneously undervalue the positive skills that women bring to business by diluting their contributions and devaluing attributes such as emotion or collaboration, while implying that women do not have the skills and behaviors, such as agency, risk-taking, or visionmaking necessary to be successful managers and leaders (Carter & Silva, 2007). This devaluation may, in part, explain why women's association of women's attributes with the role of manager declines over a four-year business undergraduate degree (Paris & Decker, 2012). At the same time, women may be deterred from developing non-stereotypical, agentive behavior, and non-traditional skills that will help them progress in the workplace.…”
Section: Discussionmentioning
confidence: 99%
“…These cases simultaneously undervalue the positive skills that women bring to business by diluting their contributions and devaluing attributes such as emotion or collaboration, while implying that women do not have the skills and behaviors, such as agency, risk-taking, or visionmaking necessary to be successful managers and leaders (Carter & Silva, 2007). This devaluation may, in part, explain why women's association of women's attributes with the role of manager declines over a four-year business undergraduate degree (Paris & Decker, 2012). At the same time, women may be deterred from developing non-stereotypical, agentive behavior, and non-traditional skills that will help them progress in the workplace.…”
Section: Discussionmentioning
confidence: 99%
“…These associations are reinforced in business textbooks (Blankenship, 2011;Pomerenke, Varner, & Mallar, 1996;Tietz, 2007). Business students are even more likely than non-business students to hold the manager D male stereotype (Paris & Decker, 2012) although business students in Hawaiʻi might be an exception (de Pillis et al, 2008).…”
Section: Do Business Students Think Of Themselves As Leaders?mentioning
confidence: 96%
“…years, the number of females majoring in and pursuing mathematics-based careers has not increased at the same speed (Berube & Glanz, 2008;Leaper et al, 2012;Paris & Decker, 2012;Sanders & Peterson, 1999). In business-related fields specifically, even though 42% of all MBA students are women, only 3.4% of the Fortune 100 Company…”
Section: Gendermentioning
confidence: 99%
“…CEOs are females (Paris & Decker, 2012). In a recent study of 439 students in a freshmen-level business mathematics course, male participants reported that they felt males alone possessed business leadership characteristics, while female participants believed that both men and women had leadership potential, though males were more likely fit for leadership roles (Paris & Decker, 2012).…”
Section: Gendermentioning
confidence: 99%
See 1 more Smart Citation